High-Valent Intermediate Observed in a Cu-Based OER Electrocatalyst by Operando X-ray Absorption Spectroscopy - Garcia-Diez, Raul; Wibowo, Romualdus Enggar; Kataev, Elmar; Quevedo Garzon, Wilson; van der Merwe, Marianne; Duarte-Ruiz, Daniel; Cocchi, Caterina; Bär, Marcus (Journal of Physical Chemistry Letters, 2025)
Understanding the chemical transformations governing the oxygen evolution reaction (OER) in Cu-based electrocatalysts is critical for advancing cost-efficient alkaline water-splitting technologies. In this study, we employ synchrotron-based operando Cu L3-edge X-ray absorption spectroscopy (XAS) and potentiodynamic techniques to probe the key intermediate species involved in alkaline OER. Our findings reveal that this metastable species exhibits an electronic structure resembling high-valent Cu complexes, particularly those associated with the CuO2- ion. Potentiodynamic measurements indicate that the high-valent intermediate emerges at potentials as low as 1.62 VRHE, coinciding with the oxidative process traditionally attributed to the Cu2+ ↔ Cu3+ redox transition, suggesting that the formation of the high-valent intermediate is directly linked to this redox process. This work provides valuable insights into the interplay between redox chemistry and catalytic performance in Cu-based OER electrocatalysts and provides further insights into the nature of the chemical species governing the oxygen evolution reaction mechanism.
CRIS-Team Scopus Importer:2025-06-27